2022
DOI: 10.1038/s41598-022-08449-w
|View full text |Cite
|
Sign up to set email alerts
|

The different overall survival between single-agent EGFR-TKI treatment and with bevacizumab in non-small cell lung cancer patients with brain metastasis

Abstract: Comparison of epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) monotherapy or with bevacizumab in real-world non-small cell lung cancer (NSCLC) patients was lacking. 310 patients of advanced NSCLC with common EGFR mutation receiving first-generation EGFR-TKI monotherapy or with bevacizumab were included and propensity-score matched. Progression-free survival (PFS), overall survival (OS) and secondary T790M mutation were analysed. Patients receiving EGFR-TKI and bevacizumab were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…36 In another real-world study analyzing the clinical outcomes of NSCLC patients with brain metastasis, the T790M-positive rate did not differ significantly between patients using an EGFR-TKI plus bevacizumab and those using EGFR-TKI monotherapy (66.7% vs. 75.0%, p = 0.460). 37 The incidence of T790M mutation was not influenced by adding different anti-VEGF agent. In a recent study evaluating the clinical outcomes of different anti-VEGF agents as an add-on therapy to an EGFR TKI, the rates of T790M detection were similar between patients using bevacizumab and ramucirumab (43.6% vs. 38.2%, p = 0.645).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…36 In another real-world study analyzing the clinical outcomes of NSCLC patients with brain metastasis, the T790M-positive rate did not differ significantly between patients using an EGFR-TKI plus bevacizumab and those using EGFR-TKI monotherapy (66.7% vs. 75.0%, p = 0.460). 37 The incidence of T790M mutation was not influenced by adding different anti-VEGF agent. In a recent study evaluating the clinical outcomes of different anti-VEGF agents as an add-on therapy to an EGFR TKI, the rates of T790M detection were similar between patients using bevacizumab and ramucirumab (43.6% vs. 38.2%, p = 0.645).…”
Section: Discussionmentioning
confidence: 94%
“…In the TERRA study, a retrospective, multicenter study conducted in Taiwan which evaluated the T790M detection rate after a first‐line combination therapy with bevacizumab and an EGFR‐TKI in advanced NSCLC, the incidence rate of T790M after acquired resistance was 55.1% 36 . In another real‐world study analyzing the clinical outcomes of NSCLC patients with brain metastasis, the T790M‐positive rate did not differ significantly between patients using an EGFR‐TKI plus bevacizumab and those using EGFR‐TKI monotherapy (66.7% vs. 75.0%, p = 0.460) 37 . The incidence of T790M mutation was not influenced by adding different anti‐VEGF agent.…”
Section: Discussionmentioning
confidence: 96%
“…It changes the tumor vessel physiology, thus increasing the intratumoral uptake of drugs. Previous studies of the administration of bevacizumab have demonstrated a clinical benefit for both primary brain tumor and brain metastasis in patients with advanced NSCLC, probably as a result of suppression of tumor angiogenesis and reduction of intracranial vasogenic edema 22,23 . In several studies, the addition of bevacizumab to first‐generation EGFR‐TKIs (gefitinib or erlotinib) significantly prolonged the PFS in patients with NSCLC with EGFR ‐activating mutations compared with gefitinib or erlotinib alone; the OS was not significantly changed 10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the administration of bevacizumab have demonstrated a clinical benefit for both primary brain tumor and brain metastasis in patients with advanced NSCLC, probably as a result of suppression of tumor angiogenesis and reduction of intracranial vasogenic edema. 22 , 23 In several studies, the addition of bevacizumab to first‐generation EGFR‐TKIs (gefitinib or erlotinib) significantly prolonged the PFS in patients with NSCLC with EGFR ‐activating mutations compared with gefitinib or erlotinib alone; the OS was not significantly changed. 10 , 13 Previous studies showed that the ORR or PFS of the osimertinib plus bevacizumab group was not superior to that of the osimertinib alone group in treatment‐naïve patients harboring EGFR ‐activating mutations, or in patients resistant to gefitinib or erlotinib who harbored the EGFR ‐T790M mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that the anti-VEGF drug bevacizumab was effective in treating brain metastasis [ 23 ], and also could significantly reduce the incidence of brain metastasis [ 24 ]. In two retrospective studies [ 25 , 26 ], bevacizumab combined with TKI prolonged the OS in patients with brain metastasis compared to TKI monotherapy. Of all the 5 RCT studies, only 2 studies [ 8 , 9 ] conducted further subgroup analysis for patients with brain metastasis, and thus only the 2 studies were included.…”
Section: Discussionmentioning
confidence: 99%